Clinical study of respiratory complications in patients undergoing elective upper abdominal surgery - C. B., Praveen; Ajmal, Imran Thariq (International Surgery Journal, 2019)
Background: Postoperative pulmonary complication is a major cause of morbidity, mortality, prolonged hospital stay and increased cost of care especially when it involves Upper Abdominal surgery. The predictable changes in lung function include a decrease in vital capacity and functional residual capacity, which are more striking in obese patients and in the supine. Aim is to study the incidence of respiratory complications in patients undergoing elective upper abdominal surgery with identification of risk factors namely Age, Sex, Obesity, Smoking and duration of upper abdominal Surgery for the development of Respiratory complications using a Peak Flow Meter as a bedside predictive test. Methods: Peak expiratory flow rate (PEFR) measurement daily up to 7 days post-surgery, were noted to monitor the occurrence of postoperative respiratory complications. Results: The study results according to our study showed that14 (34.1%) male patients out of 41 had postoperative complications as compared to 15 (48.3%) out of 31 female patients. 30.5% patients were obese and had postoperative complications of 9.75%. Overall 40% of smokers had postoperative complications. Postoperatively sub costal incision had complications (41%) in 36 patients, roof top incisions 4 out of 5 (80%) and para-umbilical incisions 3 out of 4 (75%). 80% of the patients who had upper abdominal transverse incisions developed microatelectasis followed by 75% of patients who had par median incisions. Conclusions: Respiratory complications following elective upper abdominal surgery are influenced by Increasing age and obesity and Smoking affected post-operative pulmonary recovery. Type of incision could also help change the incidence of complications.